2016
DOI: 10.1021/acsphotonics.6b00442
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Sensor Monolithically Integrated with a CMOS Photodiode

Abstract: Complementary metal oxide semiconductor (CMOS) technology has made personal mobile computing and communications an everyday part of life. In this paper we present a nanophotonic integrated CMOS-based biosensor that will pave the way for future personalized medical diagnostics. To achieve our aim, we have monolithically integrated plasmonic nanostructures with a CMOS photodiode. Following this approach of monolithic nanophotonics–microelectronics integration, we have successfully developed a miniaturized nanoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…five times lower than that measured for 0.015 refractive index change. Hence, the sensor system has a detection limit of 0.003 RIU, which is an order of magnitude better than our previous work [23]. However, working at the resolution limit of the detector induces error factors since the noise associated with electronic read-out becomes significant.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…five times lower than that measured for 0.015 refractive index change. Hence, the sensor system has a detection limit of 0.003 RIU, which is an order of magnitude better than our previous work [23]. However, working at the resolution limit of the detector induces error factors since the noise associated with electronic read-out becomes significant.…”
Section: Resultsmentioning
confidence: 79%
“…Depending on the properties of the analyte, the input wavelength can be adjusted to maximize the performance of the device for a particular analyte. From Figure 7b, we evaluated the sensitivity of the integrated sensing system to be equal to 6.5 V/RIU, which means that for a RIU change, the change in the output electrical signal is 6.5 V. The measured sensitivity value is higher than our previous work on monolithic integration of plasmonic sensors with CMOS PDs [23], [24]. The improvement of sensitivity is due to the narrower resonance linewidth of the gratings structures compared to the plasmonic structures.…”
Section: Resultsmentioning
confidence: 91%
“…Monolithic integration of both passive optical sensors and active optoelectronic devices on a single sensor chip is hence highly sought after. [ 199–201 ]…”
Section: Laboratory Prototypes Toward Poc Applicationsmentioning
confidence: 99%
“…Most of the sensing systems rely on the integration of two or more optoelectronic devices. In this context, a breakthrough in the integration of components for sensing has recently been achieved by Shakoor et al, through the combination of photonic and optoelectronic devices [172]. The authors demonstrated the monolithic integration of a plasmonic grating with a CMOS, acting as photodiode ( Figure 13).…”
Section: Towards Smart Integration Of Nanostructured Components For Tmentioning
confidence: 99%
“…The sensor is based on the monolithic integration of plasmonic nanostructures and a CMOS photodetector. © 2020 American Chemical Society, adapted with permission from [172].…”
Section: Towards Smart Integration Of Nanostructured Components For Tmentioning
confidence: 99%